Attitude and satisfaction towards electronic exams in medical sciences faculty members - Zahra Zahedi; Hamid Salehiniya; Afagh Zarei; Hamid Abbaszadeh (Tabriz University of Medical Sciences, 2021)
Background: The use of electronic exams (E-exams) has benefits in educational systems. The views of critical stakeholders, including faculty members, around E-exams should be taken into consideration in order to derive the most benefits. Due to the recent expansion of the use of E-exams at the Birjand University of Medical Sciences (BUMS), this study was conducted to assess faculty members ' attitude towards and satisfaction with E-exams. Methods: This cross-sectional study included all faculty members at the university using a census sampling method. A researcher-created questionnaire with demographic, attitude, and satisfaction sections was used to collect the data. The content validity index and the content validity ratio were used to assess validity, and Cronbach's alpha was used to assess reliability. Scoring was based on a 5-point Likert scale. SPSS was used to analyze the data using t-test and ANOVA at a significance level of 0.05. Results: Of the 126 faculty members who participated, 56.3% were women and 43.7% were men. The mean score of faculty members' attitude was 69.19±9.51 and their satisfaction score was 33.27±5.00. A significant difference was found in the mean score of attitude by faculty (P=0.038). A positive correlation was found between attitude and satisfaction (r=0.537), and attitude and satisfaction with work experience (r=0.002 and r=0.233, respectively) which indicates that the correlation between attitude and satisfaction was significant (P <0.001) Conclusion: Overall, there was a moderately positive attitude toward and a high level of satisfaction with e-exams among medical sciences faculty members. Given the correlation between attitude and satisfaction, these two categories should be taken into consideration together.